Flow behaviour in microchannels of an innovative blood analogue fluid based on giant unilamellar vesicles - Carvalho, Denise A. M. (2016)
This work focused on the development of an innovative blood analogue, containing giant unilamellar vesicles (GUVs), to mimic the flow behaviour of red blood cells (RBCs). The rheological characterization of different blood analogue solutions was performed in a stress controlled rheometer and the results have shown a good agreement when compared with a sample containing 5% of RBCs.